Enhancement of glucose uptake in muscular cell by peptide fractions separated by electrodialysis with filtration membrane from salmon frame protein hydrolysate. (April 2016) - Roblet, Cyril; Akhtar, Muhammad Javeed; Mikhaylin, Sergey; Pilon, Geneviève; Gill, Tom; Marette, André; Bazinet, Laurent
Highlights: Peptide separation by Electrodialysis with filtration membrane (EDFM). Bioactive peptides separated had high concentrations of Glu, Lys, Arg and His. 40% enhancement of glucose uptake for final feed fraction at 1 ng/mL. Synergistic effect of the peptide fraction separated by EDFM with insulin. Abstract: Consumption of fish has been positively associated with a lower risk of type 2 diabetes. In this study, the influence of pH on the separation of bioactive peptides with antidiabetic effects from Atlantic salmon frame protein hydrolysates by electrodialysis with filtration membranes (EDFM) was investigated. The results demonstrated that pH had no significant effect on final peptide concentration in either anionic (APC) or cationic peptide compartments (CPC) during EDFM but allowed the concentration of specific peptides that contained high concentrations of Glu, Ala, Lys, Arg and His residues. Moreover, the final feed compartment (FFC) and CPC after EDFM treatment at pH 6 were able to significantly enhance glucose uptake in L6 skeletal muscle cells grown in culture. The maximum enhancement of glucose uptake (40%) was demonstrated in cells treated with the FFC fraction at 1 ng/mL without insulin while a synergetic effect of FFC peptides at 1 ng/mL with insulin was observed (enhancement of glucose uptake by 31%).